Effect of sintering temperature on electrical properties of SFN ceramics doped with Al prepared by a solid-state reaction technique - Thanatep Phatungthane (2018)
© 2016 Trans Tech Publications, Switzerland. In the present work, strontium iron niobate SrFe0.5Nb0.5O3ceramics doped with aluminum were synthesized by a solid-state reaction technique. Phase formation investigation by X-ray diffraction technique (XRD) revealed that all ceramics exhibited pure perovskite phase with orthorhombic symmetry. Grain size observed by electron microscopy (SEM) was found to increase with increasing sintering temperature. The electrical properties and related parameters of the ceramics were also measured. The ceramics exhibit very good dielectric behavior and have a significant potential for dielectric applications.